Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Ultrathin polyacrylonitrile/cellulose nanofiber/hydroxyapatite composite separator regulating desolvation and ion flux for aqueous zinc-ion batteries - Xu-qiao Hu; Li-li Du; Qi-qun Lei; Shuang Zou; Fa-nian Shi; Yu-han Wu; Yu-hang Zhang; Zhe Gong; Peng-fei Wang (Chemical Engineering Journal, 2026)

Direct, catalyst-free H2O2 synthesis via scalable plasma reactor - Dongxing Li; Shao-Pei Wang; Qun Chen; Shengyan Meng; Zhaojun Zhang; Jintao Sun; Shu Liu; Cun-Feng Cheng; Qi Chen; Shui-Ming Hu; Dong H. Zhang; Annemie Bogaerts; et al. (Chemical Engineering Journal, 2026)

Solar-driven photothermal activation of peroxydisulfate for ethyl xanthate removal and reuse of mineral processing wastewater - Haoran Song; Jinyi Wu; Lechen Ren; Pu Wang; Canhai Shi; Xuewei Hu; Chen Li; Qun Zhao; Senlin Tian (Process Safety and Environmental Protection, 2026)

Vibration isolation for mechatronic metamaterial rings with piezoelectric shunting circuits - Long Zhao; Ze-Qi Lu; Li-Fang Lin; Hu Ding; Li-Qun Chen (Engineering Structures, 2026)

A-site Yb-doped CaMnO3-δ perovskite as a Co-/Sr-free oxygen electrode with enhanced conductivity and stability for solid oxide fuel cells - Qun Yang; Rengang Li; Jingxuan Hao; Hongpeng Fan; Yucheng Zhang; Yue Hu; Xiao Lin; Linjuan Zhang; Dehua Zheng; Zaifeng Li; Jian-Qiang Wang (Chemical Engineering Journal, 2026)

An Interpretable Machine Learning Model for Predicting the Presence of Talaromycosis in HIV Patients Lacking Skin Lesions - Jiaguang Hu; Wenming He; Qun Tian; Yanqiu Lu; Peng Zhang; Jinyu Qin; Chuan Qin; Ying Wu; Cheng Huang; Xu Li; Luhuai Feng; Linghua Li; et al. (Mycopathologia, 2026)
Introduction The existing predictive models for talaromycosis in people living with HIV without skin lesions are limited by established risk factors and traditional statistical approaches. This study aims to develop an interpretable machine learning(ML) model for predicting the presence of talaromycosis in HIV patients without skin lesions and to validate its clinical applicability. Methods This retrospective multicenter study involved the analysis of electronic medical records from four tertiary hospitals in China, covering the period from 2010 to 2019. The training dataset comprised 1009 HIV patients with opportunistic infections, while external validation was conducted using data from 305 patients at an independent center. From an initial set of 36 variables, twelve key features were selected, including albumin, absolute lymphocyte count, hemoglobin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST/ALT ratio, C-reactive protein, white blood cell count, platelet count, peripheral or abdominal lymphadenopathy, CD4 + T-cell count, and age. Five ML algorithms were evaluated using tenfold cross-validation. Model performance was measured using the AUC, ACC, and F1-score. Calibration curves and decision curve analysis (DCA) were employed to assess the model’s reliability and clinical net benefit. The optimal model was subsequently implemented as a web-based tool. Results The Support Vector Machine (SVM) exhibited superior performance compared to other models, achieving an AUC of 0.809 (95% CI 0.778–0.838), an ACC of 0.714, and an F1-score of 0.689. External validation demonstrated enhanced performance metrics, with an AUC of 0.921 (95% CI 0.889–0.951), ACC of 0.853, and an F1-score of 0.819. DCA indicated a significant net clinical benefit across various risk thresholds, and calibration curves showed strong concordance between predicted and observed risks. Conclusion The interpretable SVM model effectively stratifies the risk of talaromycosis in people living with HIV without skin lesions in endemic regions, aligning with WHO recommendations for early diagnosis and treatment of priority fungal pathogens. Its integration into a web-based tool enhances clinical accessibility for early intervention in resource-constrained settings.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Structural dynamics of chloroplast genome in Paphiopedilum (Orchidaceae): in response to natural hybridization - Xue-Ying Wei; Ai-Qun Hu; Jin Zhou; Jiang-Ping Shu; Wei-Yue Sun; Li-Qiang Li; Jian-Wen Shao; Hui Wang; Yue-Hong Yan (Molecular Phylogenetics and Evolution, 2026)

Synergistic optimization of yield, quality, and nitrogen use efficiency in indica rice: Influence of nitrogen management and C-N metabolism linkages - Hongjin Li; Tao Li; Jianghui Yu; Tianyu Du; Ping Zhang; Jingjing Cui; Zheshu Xu; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; Guangyan Li; et al. (Field Crops Research, 2026)

Activation of peroxymonosulfate by MXene-confined micron-sized copper particle catalyst: A new understanding of size effects - Haoran Song; Xudong Zhang; Mengting Guo; Pu Wang; Jie Li; Chen Li; Yan Cao; Linfeng Zhang; Qun Zhao; Xuewei Hu; Senlin Tian (Chemical Engineering Journal, 2026)

Feasibility of the constructed Technosols prepared solely from concrete recycled aggregates as a plant growth medium - Fengrui Zi; Qun Zhao; Haiyan Chen; Zhangqian Wu; Wenxing Li; Haoran Song; Jianhong Huang; Jie Li; Xuewei Hu; Senlin Tian (Journal of Soils and Sediments, 2026)

Quantifying the nonlinear interactions of 2D/3D building and green space morphology on land surface temperature across different urban functional zones - Haiyan Luo; Rui Zhou; Chunlin Li; Qun Ma; Xuening Fang; Yina Hu; Xinlin Lv; Zining Dong; Yujing Tian; Shubo Fang (Sustainable Cities and Society, 2026)

Magnetic organic frame material Fe3O4@Au/COF for sensitive SERS detection and photo-Fenton degradation of tetracycline - Yalin Xie; Chenxi Yi; Qun Zhou; Min Hu; Panjie Li; Xiaojun Luo; Yuanyuan Li (Journal of Environmental Chemical Engineering, 2025)

Sustainable thermochromic coatings for pavement cooling and carbon offset under climate change - Yujing Chen; Aimin Sha; Wei Jiang; Wenxiu Jiao; Yangsen Cao; Xinzhou Li; Xiaotong Du; Kui Hu; Qun Lu (Transportation Research Part D: Transport and Environment, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

The topographic-related subsurface heat transport processes during the MJO propagation across the Maritime Continent - Kecheng Lu; Haibo Hu; Xiu-Qun Yang; Yiran Li; Peilong Yu; Kefeng Mao; Shengyi Qian; Ziyi Wang (Climate Dynamics, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

Amplified toxic effects of nanoplastic composite norfloxacin on liver cells in mice: Mechanistic insights and multiscale evaluation - Hengyu Song; Guidong Gao; Yanmei Lei; Qun Wu; Xiangxiang Li; Shuqi Guo; Yuntao Qi; Tingting Wang; Shaoyang Hu; Rutao Liu (Environmental Pollution, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Co-Exposure of airborne microplastics and chromium: Impairment of pulmonary surfactant monolayer - Linfeng Zhang; Yan Cao; Jie Li; Chao Li; Yanlin Yang; Jiao Li; Xuewei Hu; Xiangfen Cui; Qun Zhao; Haoran Song; Jianhong Huang; Senlin Tian (Journal of Hazardous Materials, 2025)

Discovery of indole-carbohydrazide hybrids as novel broad-spectrum fungicidal lead compound though membrane-targeting mechanism - Ying Wu; Li-Hui Shao; Xian-Qun Hu; Yu Long; Yuan-Yuan Wu; Pei-Bu Yu; Ai-Ping Yan; Long-Fei Li; Xiang Zhou; Song Yang (Molecular Diversity, 2025)

Remediation of lead and arsenic co-contaminated soils using self-sustaining smoldering: Performance and mechanism - Jie Li; Haiyan Chen; Fengrui Zi; Zhangqian Wu; Xiangfen Cui; Haoran Song; Jianhong Huang; Qun Zhao; Xuewei Hu; Senlin Tian (Journal of Environmental Chemical Engineering, 2025)

Construction of new thermostable MtLPMO9V in synergism with cellulases for efficient lignocellulosic hydrolysis - Weimeng Li; Hang Yuan; Yun Hu; Shaohua Dou; Ezhen Zhang; Qun Wu; Fubao Sun (Bioresource Technology, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Atmospheric CO2 and CH4 observations in Hangzhou before, during, and after the 2023 Asian Games: Insights from vehicle-carried and fixed stations - Tianhao Wang; Jiansen Wang; Ning Hu; Ruonan Li; Meng Shan; Qun Lin; Longlong Chen; Jun Wang; Yuxin Jiang; Zhonghao Yang; Wei Xiao (Atmospheric Pollution Research, 2025)

Chermesins I-N: Bioactive spiromeroterpenoids from the marine-sourced fungus Penicillium chermesinum AS-400 - Yi-Wei Liu; Xue-Yi Hu; Xiao-Dan Chen; Xiao-Ming Li; Sui-Qun Yang; Hong-Lei Li; Bin-Gui Wang (Phytochemistry, 2025)

Aggregation behavior of photoaging nanoplastics in artificial sweat solutions - Yanlin Yang; Haoran Song; Yan Cao; Jiao Li; Jie Li; Xiangfen Cui; Xuewei Hu; Anjum Mahfuza; Ping Ning; Linfeng Zhang; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2025)

Differences in starch and protein composition, morphological and structure, and their impacts on eating quality of soft japonica rice under different light and nitrogen fertilizer conditions in southern China - Zhongtao Ma; Jianghui Yu; Xi Chen; Jiale Cao; Ying Zhu; Guodong Liu; Guangyan Li; Fangfu Xu; Qun Hu; Hongcheng Zhang; Haiyan Wei (Food Chemistry, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Nutrient addition alters drought resistance and resilience via forb abundance in a temperate grassland - Dengnan Luo; Guojiao Yang; Guangru Zhang; Qianguang Liu; Qun Guo; Shenggong Li; Yun Xie; Zhongmin Hu (Agriculture, Ecosystems & Environment, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Improving the prebiotic activity and oxidative stability of carboxymethyl curdlan − quercetin conjugates stabilized Pickering emulsions for the colonic targeting delivery of curcumin - Huan Li; Wenjiang He; Zijun Wang; Qun Zhang; Die Hu; Ke Ding; Qiutao Xie; Yanqun Xu; Yang Shan; Shenghua Ding (Food Research International, 2025)

Origin of the coeval Nb-enriched and arc mafic igneous rocks: Implications for Paleozoic tectonic evolution of the Southwestern Tianshan - Li-Tao Ma; Li-Qun Dai; Ye-Dan Hu; Zi-Fu Zhao (Chemical Geology, 2025)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Interaction of diesel exhaust particulate matter with mucins in simulated saliva fluids: Bioaccessibility of heavy metals and potential health risks - Jiao Li; Haorang Song; Linfeng Zhang; Jie Li; Yanlin Yang; Xiangfen Cui; Anjum Mahfuza; Yan Cao; Xuewei Hu; Chen Li; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2024)

Environmental exposure to cadmium induces olfactory neurotoxicity in fire ants and the molecular basis - Xiaohui Xiao; Wenzhen Zhao; Yikang Shao; Changyuan Hu; Jinlong Liu; Guoqing Zhang; Fuxiang Yang; Jing Zhao; Yueguan Fu; Lei Li; Man-Qun Wang; Aiming Zhou (Environmental Pollution, 2024)

MXene-supported Co3Ti and single-atom Co catalyst activated PMS for efficient removal of Pb-EDTA: The involvement of Co (Ⅳ) - Haoran Song; Longyu Chen; Yi hang Xu; Chen Li; Xuewei Hu; Yingjie Li; Shugen Liu; Jianhong Huang; Qun Zhao; Jie Li; Senlin Tian (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

A facile and intelligent detection method for diclazuril based on a stable dual emissive Eu3+-dopped metal–organic framework - Yi-Fan Xia; Yan-Xia Li; Qing-Yan Xiao; Zhi-Qiang Cai; Qian-Wen Yang; Yi-Xuan Hu; Zi-Yi Mei; Guang-Ming Bao; Hou-Qun Yuan (Food Chemistry, 2024)

An investigation of a self-powered low-frequency nonlinear vibration isolation system - Ze-Qi Lu; Rong-Biao Hao; Dao Wu; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

Secular mantle wedge evolution due to variable slab fluid metasomatism: Evidence from Permian-Triassic mafic igneous rocks in the Paleo-Tethys tectonic regime - Ye-Dan Hu; Li-Qun Dai; Li-Tao Ma; Zi-Fu Zhao (Chemical Geology, 2024)

Exposure to O3 and NO2 on the interfacial chemistry of the pulmonary surfactant and the mechanism of lung oxidative damage - Jie Li; Haoran Song; Tao Luo; Yan Cao; Linfeng Zhang; Qun Zhao; Zhanchao Li; Xuewei Hu; Junjie Gu; Senlin Tian (Chemosphere, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

A state-of-the-art review on the dynamic design of nonlinear energy sinks - Xiao-Feng Geng; Hu Ding; Jin-Chen Ji; Ke-Xiang Wei; Xing-Jian Jing; Li-Qun Chen (Engineering Structures, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Dual N-linked glycosylation at residues 133 and 158 in the hemagglutinin are essential for the efficacy of H7N9 avian influenza virus like particle vaccine in chickens and mice - Yufei Wang; Qun Li; Peipei Peng; Qi Zhang; Yalan Huang; Jiao Hu; Zenglei Hu; Xiufan Liu (Veterinary Microbiology, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

Parametric resonance of pipe conveying pulsating fluid with initial geometric imperfection - Meng-Yuan Hao; Hu Ding; Xiao-Ye Mao; Sha Wei; Li-Qun Chen (Ocean Engineering, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

The implications of lipid mobility, drug-enhancers (surfactants)-skin interaction, and TRPV1 activation on licorice flavonoid permeability - Zhuxian Wang; Hongkai Chen; Tao Liang; Yi Hu; Yaqi Xue; Yufan Wu; Quanfu Zeng; Yixin Zheng; Yinglin Guo; Zeying Zheng; Dan Zhai; Peiyi Liang; et al. (Drug Delivery and Translational Research, 2024)

Associations of metals and metal mixtures with glucose homeostasis: A combined bibliometric and epidemiological study - Kai Li; Yisen Yang; Jiaxin Zhao; Quan Zhou; Yanbing Li; Ming Yang; Yaoyu Hu; Jing Xu; Meiduo Zhao; Qun Xu (Journal of Hazardous Materials, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Membrane Trafficking-Related Genes Predict Tumor Immune Microenvironment and Prognosis in Colorectal Cancer - Zhou Ding; Lu Han; Qun Zhang; Jing Hu; Li Li; Xiaoping Qian (Biochemical Genetics, 2024)

Interactions between inhalable aged microplastics and lung surfactant: Potential pulmonary health risks - Yan Cao; Qun Zhao; Fanshu Jiang; Yingxue Geng; Haoran Song; Linfeng Zhang; Chen Li; Jie Li; Yingjie Li; Xuewei Hu; Jianhong Huang; Senlin Tian (Environmental Research, 2024)

Forced resonance of a buckled beam flexibly restrained at the inner point - Jie Jing; Zhi-Hua Shao; Xiao-Ye Mao; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

The mediating role of accelerated biological aging in the association between blood metals and cognitive function - Kai Li; Jingtao Wu; Quan Zhou; Jiaxin Zhao; Yanbing Li; Ming Yang; Yisen Yang; Yaoyu Hu; Jing Xu; Meiduo Zhao; Qun Xu (Journal of Hazardous Materials, 2024)

Blasingame production decline curve analysis for fractured tight sand gas wells based on embedded discrete fracture model - Xianshan Liu; Shaoyang Geng; Peng Hu; Yao Li; Runhua Zhu; Shudong Liu; Qun Ma; Chengyong Li (Gas Science and Engineering, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Nine pairs of undescribed enantiomers from the resin of Styrax tonkinensis (Pierre) Craib ex Hart with anti-inflammatory activity - Qun Li; Hong-Bin Fang; Bin-Yuan Hu; Yong-Ming Yan; Ya-Bin Jiao; Gan-Peng Li; Yong-Xian Cheng (Phytochemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Quantifying the effects of urban development intensity on the surface urban heat island across building climate zones - Tianxing He; Rui Zhou; Qun Ma; Chunlin Li; Dan Liu; Xuening Fang; Yina Hu; Jun Gao (Applied Geography, 2023)

Occurrence and risk assessment of organophosphate esters in global aquatic products - Luyao Gu; Boyuan Hu; Yilin Fu; Wei Zhou; Xiaomin Li; Kai Huang; Qun Zhang; Jie Fu; Haiyan Zhang; Aiqian Zhang; Jianjie Fu; Guibin Jiang (Water Research, 2023)

Static bifurcation and nonlinear vibration of pipes conveying fluid in thermal environment - Xiao-Ye Mao; Si-Yu Gao; Hu Ding; Li-Qun Chen (Ocean Engineering, 2023)

Removal of cadmium in contaminated soils by self-sustaining smoldering - Jie Li; Qun Zhao; Meiyan Si; Zejing Dong; Jianhong Huang; Yingjie Li; Xuewei Hu; Senlin Tian (Journal of Environmental Chemical Engineering, 2023)

Cascade reaction-based highly sensitive fluorescent sensing systems applicable for dual-pattern fluorescence visualizing of thiophenol flavors in meat products and condiments - Zi Yi Xu; Xiao Hu Wang; Hong Qun Luo; Nian Bing Li (Food Chemistry, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Global/local buckling analysis of thin-walled I-section beams via hierarchical one-dimensional finite elements - Yichen Yang; Yanchuan Hui; Ping Li; Jie Yang; Qun Huang; Gaetano Giunta; Salim Belouettar; Heng Hu (Engineering Structures, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Apigenin inhibits growth of melanoma by suppressing miR-512-3p and promoting the G1 phase of cell cycle involving the p27 Kip1 protein - Qun Xie; Ruirui Zhang; Dandan Liu; Jing Yang; Qiang Hu; Chao Shan; Xiaohan Li (Molecular and Cellular Biochemistry, 2022)

Detoxification of aflatoxin B 1 in broiler chickens by a triple-action feed additive - Hongwei Guo; Juan Chang; Ping Wang; Qingqiang Yin; Chaoqi Liu; Silu Li; Qun Zhu; Mingfan Yang; Xiaofei Hu (Food Additives & Contaminants: Part A, 2021)

Identification of immune-related gene signature predicting survival in the tumor microenvironment of lung adenocarcinoma - Mengnan Zhao; Ming Li; Zhencong Chen; Yunyi Bian; Yuansheng Zheng; Zhengyang Hu; Jiaqi Liang; Yiwei Huang; Jiacheng Yin; Cheng Zhan; Mingxiang Feng; Qun Wang (Immunogenetics, 2020)

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Rescue and characterization of a recombinant HY12 bovine enterovirus carrying a foreign HA epitope in the 3A nonstructural protein - Dan Liu; Changming Liu; Xing Liu; Xin Li; Liping Huang; Junying Hu; Yanwu Wei; Hongzhen Zhu; Qun Zhang; Xinping Wang (Archives of Virology, 2019)

Shifts in the dynamics of productivity signal ecosystem state transitions at the biome‐scale - Zhongmin Hu; Qun Guo; Shenggong Li; Shilong Piao; Alan K. Knapp; Philippe Ciais; Xinrong Li; Guirui Yu (Ecology Letters, 2018)
Understanding ecosystem dynamics and predicting directional changes in ecosystem in response to global changes are ongoing challenges in ecology. Here we present a framework that links productivity dynamics and ecosystem state transitions based on a spatially continuous dataset of aboveground net primary productivity ( ANPP ) from the temperate grassland of China. Across a regional precipitation gradient, we quantified spatial patterns in ANPP dynamics (variability, asymmetry and sensitivity to rainfall) and related these to transitions from desert to semi‐arid to mesic steppe. We show that these three indices of ANPP dynamics displayed distinct spatial patterns, with peaks signalling transitions between grassland types. Thus, monitoring shifts in ANPP dynamics has the potential for predicting ecosystem state transitions in the future. Current ecosystem models fail to capture these dynamics, highlighting the need to incorporate more nuanced ecological controls of productivity in models to forecast future ecosystem shifts.

Tau-Induced Ca2+/Calmodulin-Dependent Protein Kinase-IV Activation Aggravates Nuclear Tau Hyperphosphorylation - Yu-Ping Wei; Jin-Wang Ye; Xiong Wang; Li-Ping Zhu; Qing-Hua Hu; Qun Wang; Dan Ke; Qing Tian; Jian-Zhi Wang (Neuroscience Bulletin, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Impact of land use conversion on soil organic carbon stocks in an agro-pastoral ecotone of Inner Mongolia - Wei Zhao; Zhongmin Hu; Shenggong Li; Qun Guo; Hao Yang; Tonghui Zhang (Journal of Geographical Sciences, 2017)

A synthesis of the effect of grazing exclusion on carbon dynamics in grasslands in China - Zhongmin Hu; Shenggong Li; Qun Guo; Shuli Niu; Nianpeng He; Linghao Li; Guirui Yu (Global Change Biology, 2016)
Grazing exclusion ( GE ) is considered to be an effective approach to restore degraded grasslands and to improve their carbon (C) sequestration. However, the C dynamics and related controlling factors in grasslands with GE have not been well characterized. This synthesis examines the dynamics of soil C content and vegetation biomass with the recovery age through synthesizing results of 51 sites in grasslands in China. The results illustrate increases in soil C content and vegetation biomass with GE at most sites. Generally, both soil C content and vegetation biomass arrive at steady state after 15 years of GE . In comparison, the rates of increase in above‐ and belowground biomass declined exponentially with the age of GE , whereas soil C content declined in a milder (linear) way, implying a lagged response of soil C to the inputs from plant biomass. Mean annual precipitation ( MAP ) and the rate of soil nitrogen (N) change were the main factors affecting the rate of soil C content change. MAP played a major role at the early stage, whereas the rate of soil N change was the major contributor at the middle and late stages. Our results imply that the national grassland restoration projects in China may be more beneficial for C sequestration in humid regions with high MAP . In addition, increased soil N supply to grasslands with GE at the latter recovery stage may enhance ecosystem C sequestration capacity.

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Molecular mapping and markers for leaf rust resistance gene Lr24 in CIMMYT wheat line 19HRWSN-122 - Ai-yong Qi; Pei-pei Zhang; Xian-chun Xia; Zhong-hu He; Julio Huerta-Espino; Zai-feng Li; Da-qun Liu (Euphytica, 2015)

Identification and mapping of a novel blast resistance gene Pi57(t) in Oryza longistaminata - Peng Xu; Liying Dong; Jiawu Zhou; Jing Li; Yu Zhang; Fengyi Hu; Shufang Liu; Qun Wang; Wei Deng; Xianneng Deng; Didier Tharreau; Qinzhong Yang; et al. (Euphytica, 2015)

Paenibacillus nicotianae sp. nov., isolated from a tobacco sample - Qing-Qing Li; Xing-Kui Zhou; Li-Zhi Dang; Juan Cheng; Wael N. Hozzein; Min-Jiao Liu; Qun Hu; Wen-Jun Li; Yan-Qing Duan (Antonie van Leeuwenhoek, 2014)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Diffusion tensor imaging reveals evolution of primate brain architectures - Degang Zhang; Lei Guo; Dajiang Zhu; Kaiming Li; Longchuan Li; Hanbo Chen; Qun Zhao; Xiaoping Hu; Tianming Liu (Brain Structure and Function, 2013)

Characterization of embryogenesis and early larval development in the Pacific triton, Charonia tritonis (Gastropoda: Caenogastropoda) - Lü-Ping Zhang; Jian-Jun Xia; Peng-Fei Peng; Hai-Peng Li; Peng Luo; Chao-Qun Hu (Invertebrate Reproduction & Development, 2013)

Effect of Fluoride on Insulin Level of Rats and Insulin Receptor Expression in the MC3T3-E1 Cells - Chun-yan Hu; Li-qun Ren; Xi-ning Li; Nan Wu; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2012)

Spatial variations in aboveground net primary productivity along a climate gradient in Eurasian temperate grassland: effects of mean annual precipitation and its seasonal distribution - Qun Guo; Zhongmin Hu; Shenggong Li; Xuanran Li; Xiaomin Sun; Guirui Yu (Global Change Biology, 2012)
Concomitant changes of annual precipitation and its seasonal distribution within the context of global climate change have dramatic impacts on aboveground net primary productivity ( ANPP ) of grassland ecosystems. In this study, combining remote sensing products with in situ measurements of ANPP , we quantified the effects of mean annual precipitation ( MAP ) and precipitation seasonal distribution ( PSD ) on the spatial variations in ANPP along a climate gradient in Eurasian temperate grassland. Our results indicated that ANPP increased exponentially with MAP for the entire temperate grassland, but linearly for a specific grassland type, i.e. the desert steppe, typical steppe, and meadow steppe from arid to humid regions. The slope of the linear relationship appeared to be steeper in the more humid meadow steppe than that in the drier typical and desert steppes. PSD also had significant effect on the spatial variations in ANPP . It explained 39.4% of the spatial ANPP for the entire grassland investigated, being comparable with the explanatory power of MAP (40.0%). On the other hand, the relative contribution of PSD and MAP is grassland type specific. MAP exhibited a much stronger explanatory power than PSD for the desert steppe and the meadow steppe at the dry and wet end, respectively. However, PSD was the dominant factor affecting the spatial variation in ANPP for the median typical steppe. Our results imply that altered pattern of PSD due to climate change may be as important as the total amount in terms of effects on ANPP in Eurasian temperate grassland.

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Increased cortico-subcortical functional connectivity in schizophrenia - Degang Zhang; Lei Guo; Xintao Hu; Kaiming Li; Qun Zhao; Tianming Liu (Brain Imaging and Behavior, 2012)

Mutations in exons of the CYP17-II gene affect sex steroid concentration in male Japanese flounder (Paralichthys olivaceus) - Ruiqin Ma; Feng He; Haishen Wen; Jifang Li; Bao Shi; Dan Shi; Miao Liu; Weijie Mu; Yuanqing Zhang; Jian Hu; Weiguo Han; Jianan Zhang; et al. (Journal of Ocean University of China, 2012)

Dominant Contribution of Northern Chinese to the Paternal Genetic Structure of Chaoshanese in South China - Sheng-Ping Hu; Hui Li; Feng-Huan Zhang; Li-Qun Huang; Yan Lu (Biochemical Genetics, 2011)

Functional Annotation and Analysis of Expressed Sequence Tags from the Hepatopancreas of Mitten Crab (Eriocheir sinensis) - Hui Jiang; Yi-Mei Cai; Li-Qiao Chen; Xiao-Wei Zhang; Song-Nian Hu; Qun Wang (Marine Biotechnology, 2009)

T1 locus in cotton is the candidate gene affecting lint percentage, fiber quality and spiny bollworm (Earias spp.) resistance - Qun Wan; Zhengsheng Zhang; Meichun Hu; Li Chen; Dajun Liu; Xiao Chen; Wei Wang; Jing Zheng (Euphytica, 2007)